Load Description and Damage Evaluation Using Vehicle Independent Driving Events. (2015) - Maghsood, Roza; Rychlik, Igor; Johannesson, Pär
Abstract: We consider the loads that are related to steering events, and focus on the events that cause high forces on steering components. The load is simplified by keeping the extreme force value for each driving event. We define a simplified stochastic model for the load by modeling the extreme value for each driving event by a random variable. We give formulas to compute the theoretical load spectrum and the expected fatigue damage caused by the driving events. Further, in a sensitivity study we investigate how much the expected damage depends on the variability of parameters of the proposed model.